(3JNejS TPhQ GdPgHs - (3HQgGf GdOjf Ydj GdeYQha HGHf GQaY QGSgs; (3CHh eMeO LeGd GdOjf YHO Gddg Hf jhSa GHf gTGe GdfMhj,J (B762 (3g` s ((3eMeO Hf jMji Hf CMeO s)
(3ChdgG (B:s
(3bGd GdTjN GdeYQha HGHf GQaY QCS QMeg Gddg JYGdi bGajI GdGda GdChdi Ydi GHjGJ JYde bO hGdYde GdYRjR efHGA HeG gh SQ ai GdRehQ eNHC ceGdcg ajg WQjb ehWC ZPG KdK GdQjM HGdRgQI GeQA s
(3BNQgG (B:s
(3hEdG adG JQjY HgG agi QhVJg bO EeJdCJ ddQGFOjf CaGYjG s
(3GdcQGSI GdChdi HNW MOjKs
(3HBNQgG ebGHdIs
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHI s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
Keywords: (3GdfMhs